Analysis of Intervention Effect and Satisfaction of Holistic Nursing after Oral Tumor Resection. (15th July 2022) - Qu, Lingling; Yin, Yan; Zhao, Na; Lv, Yongmei; Xu, Hangyong
Abstract : Objective . To explore the intervention effect and satisfaction analysis of holistic nursing after oral tumor resection. Methods . A total of 70 oral tumor patients who underwent surgical treatment in our hospital from April 2020 to September 2021 were randomly divided into two groups, with 35 patients in each group. The control group was given basic oral care, the observation group was given overall oral care, and the actual effects of the two groups of care were compared, including the emotional status, compliance and nursing satisfaction, hospital stay and nursing quality scores, pain level, quality of life, and complications occurred. Results . After nursing, the patients in the observation group had good mood, higher compliance and nursing satisfaction, shorter hospital stay, higher nursing quality and quality of life scores, lower pain level, and lower incidence of complications, when compared with the control group. Conclusion . Holistic nursing has obvious effects on patients after oral tumor surgery, which can relieve patients' negative emotions, improve patients' compliance with treatment, improve their quality of life, and effectively reduce the degree of pain and the occurrence of complications, which is worthy of clinical promotion.